Arabic as Second Language of Educated Generation: A Theoretical Analysis at Islamic Educational Institutions in Indonesia - Rayinda Dwi Prayogi; Sudharno Shobron (Ittishal Educational Research Journal, 2020)
Arabic has been chosen as a medium of the revealed language for every language speakers in the world. Arabic is a language which rich in vocabulary and also as an intact language which has the system and style of language to overcome other languages. This language is the language of science, civilization, and intellectuality from the past until now and later. No wonder, Allah SWT has placed it on the highest maqqom (position) as the Qur'anic language. The Qur'an is something that must be understood and appreciated, or even made as second language by the unique Indonesian society (it is the largest moslem population but its national language is latin) especially by educated generations of Islamic educational institutions. The classic problem faced by moslems in Idonesia is the lack of understanding and appreciating of Islamic values ​​due to the weakening of arabic. It is interesting to be learned and deepened as the reflection and improvement of religious behavior of society and specialized for Islamic Educational Institutions that create moslem generation. This article will discuss the role of Islamic Education Institutions in Indonesia in Arabic learning process and also approaches used Arabic language acquisition until placed it become second language.